Unravelling the Impact: Academic Stress and Its Role in Shaping Learning Approaches Among Paramedical Students – A Cross-Sectional Study - Zahid Zia, Pirzada; Dorai B, Lakshmi; Sumaira, Sumaira; Pradeep. C, Pradeep. C (Journal of Neonatal Surgery, 2025)
the function heredity plays in mood regulation. Longitudinal studies, customized therapies, and incorporating mental health assistance into standard medical care should be the main topics of future research. Healthcare professionals can create more effective plans to assist menopausal women and lessen the stigma associated with this transition by filling in these gaps.